Neural synchronization analysis of electroencephalography coherence in patients with Parkinson's disease-related mild cognitive impairment. (2022) - Mano, Tomoo; Kinugawa, Kaoru; Ozaki, Maki; Kataoka, Hiroshi; Sugie, Kazuma
Highlights: We studied brain functional connectivity in 20 patients with PD-MCI and 10 MCI patients without Parkinsonism. Cognitive impairment was related to decreased coherence in the alpha range. Regional coherence in left FP had a higher correlation with cognitive function. Differences in EEG coherence may reflect a compensatory response to PD-MCI. Abstract: Introduction: The underlying pathophysiology of slight cognitive dysfunction in Parkinson's disease-related mild cognitive impairment (PD-MCI) is yet to be elucidated. Our study aimed to evaluate the association between cognitive function and brain functional connectivity (FC) in patients with PD-MCI. Methods: Twenty patients with sporadic PD-MCI were evaluated for FC in the brain network. Further, electroencephalography (EEG) coherence analysis in the whole-brain and quantified regional coherence using phase coupling were performed for each frequency, and motor and cognitive function were assessed in the whole-brain. Results: The degree of cognitive impairment was related to a decrease in the coherence in the alpha ranges. The regional coherence in the left frontal-left parietal region rather than the right frontal-right parietal region showed a higher correlation with the cognitive function scores. Conclusion: The differences in EEG coherence across different types of cognitive dysfunction reflect a compensatory response to the heterogeneous and complex clinical presentation of PD-MCI. Our findings indicate decreased brain efficiency and impaired neural synchronization in PD-MCI; these results may be crucial in elucidating the pathological exacerbation of PD-MCI.